Towards a Prosperous Indonesia: Building the Local Economy Through Food Estates in Sukodono, Gresik - Nurlaila Tria Agustina; Aisyah Salsabila; Akmal Naufal; Novi Lailiyul Wafiroh (International Journal of Asian Business and Management, 2024)
Indonesia has a food estate program which is a program initiated to make Indonesia developed. Food estate program under the auspices of the government which aims to increase national food security. One of the food estate programs is established in Sukodono Village, because it has the potential to develop the local economy of the community. The aim of this qualitative research is to find out how the food estate program in Sukodono Village is run and how it impacts the community. This research uses a literature study approach which focuses on the data collection process through interviews, observation, documentation and literature study. The research results show that the Sukodono Village food estate program has made progress, but also has problems. Problems with the government, human resources (HR) which are still not fully supported, and problems with the distribution of agricultural products. The condition of other food estates is considered progress due to synchronization with the village green house program to improve economic welfare